Laboratory Evaluation Links Some False-Positive COVID-19 Antigen Test Results Observed in a Field Study to a Specific Lot of Test Strips. (5th January 2023) - Carter, Alyssa M; Viloria Winnett, Alexander; Romano, Anna E; Akana, Reid; Shelby, Natasha; Ismagilov, Rustem F
Abstract: During a household-transmission field study using COVID-19 antigen rapid diagnostic tests (Ag-RDT), a common test strip lot was identified among 3 participants with false-positive results. In blinded laboratory evaluation, this lot exhibited a significantly higher false-positive rate than other lots. Because a positive Ag-RDT result often prompts action, reducing lot-specific false positives can maintain confidence and actionability of true-positive Ag-RDT results.